2011
DOI: 10.4028/www.scientific.net/amr.236-238.2307
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Microencapsulated Cinnamon Oil and Its Application on Cherry Tomato

Abstract: In this investigation, antibacterial property of microencapsulated cinnamon oil was investigated. Microencapsulated cinnamon oil was prepared by simple coacervation. Microencapsulated cinnamon oil exhibited good antimicrobial activities.Moreover, the effect of microencapsulated cinnamon oil on the quality of cherry tomato was investigated. Result showed microencapsulated cinnamon oil could reduced fruit decay and keep the quality of cherry tomato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…) and 0.3 g of microencapsulated rosemary and thyme oils (MRO and MTO) (Xing et al. ) were used. Button mushrooms were placed in polyethylene (PE) film packaging, with filter paper inside the cover.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…) and 0.3 g of microencapsulated rosemary and thyme oils (MRO and MTO) (Xing et al. ) were used. Button mushrooms were placed in polyethylene (PE) film packaging, with filter paper inside the cover.…”
Section: Methodsmentioning
confidence: 99%
“…Button mushrooms sporophores from the local market of Esfahan city were selected for uniform size, maturity, and absence of mechanical damage. Five lLÁL À1 each of rosemary and thyme oils (RO and TO) (Gao et al 2014) and 0.3 g of microencapsulated rosemary and thyme oils (MRO and MTO) (Xing et al 2011) were used. Button mushrooms were placed in polyethylene (PE) film packaging, with filter paper inside the cover.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous studies have documented the antifungal effect of plant essential oils to control food spoilage fungi (Tzortzakis, 2009;Dulce et al, 2010;Shirzad et al, 2011;Tian et al, 2011;Xing et al, 2011;Tabaestani et al, 2013 ;Chen et al, 2014;Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al (2011) reported that results of both in vitro and in vivo studies on fungal spoilage of cherry tomatoes indicate that employing dill (Anethun graveolens L.) oil as a significant potential fumigant against A. alternata and Aspergillus spp extended usual storage and transport period is very promising. Xing et al (2011) suggested that microencapsulated cinnamon oil could reduce cherry tomato fruits decay and keep their quality.…”
Section: Introductionmentioning
confidence: 99%